Hello I Struggle Heavily With Proof For Universal And Existential Statements

Hello. I could use some help with this proof. I struggle heavily with proof for universal and existential statements. The task is to construct a proof using the given premise to reach the given conclusion. I’m not too sure how to approach this.

The proof is as follows.

Premise:

∀x (Cube(x) → ∀y (Dodec(y) → Larger(x, y)))

∀x (Dodec(x) → ∀y (Tet(y) → Larger(x, y)))

∃x Dodec(x)

Conclude:

∀x (Cube(x) → ∀y (Tet(y) → Larger(x, y)))

Posted in Uncategorized